GC-MS analysis and nutra-pharmaceutical potential of Mentha piperita essential oil extracted by supercritical fluid extraction and hydro-distillation - Abbas, Ali; Anwar, Farooq; Ahmad, Naveed; Rehman, Afifa tur; Mohammed, Osama A.; Abdel-Reheim, Mustafa Ahmed; Iqbal, Munawar; Iqbal, Shahid; Nazir, Arif (Elsevier Ltd, 2024)
This study reports the comparative evaluation of yield, physico-chemical composition and biological attributes (antioxidant activity, antimicrobial activity, biofilm inhibition and hemolytic activity) of peppermint (Mentha piperita L.) essential oil (EO) obtained by hydro-distillation (HD) and supercritical fluid (CO2) extraction (SCFE) methods. The yield (%) of EO obtained by HD (0.20 %) was significantly (p < 0.05) higher than that of SCFE (0.13 %) while the variation in the physical parameters like solubility, color, density (at 25 °C) and refractive index (at 25 °C) was not significant between the tested oils. The data of chemical compositional analysis revealed that menthol was the key component in the EO obtained by HD (52.85 %) and SCFE (45.51 %), followed by menthone [HD (25.93 %) and SCFE (27.3 %)] and eucalyptol [HD (8.59 %); SCFE (8.92 %)]. The EO extracted with supercritical fluid (SCFE-EO) exhibited superior (p < 0.05) DPPH free radical inhibition potential (52 %) with an IC50 value of 15.65 μg/mL and reducing power compared to that of HD-EO. The highest antimicrobial activity was exhibited by SCFE-EO against Pasturella multocida with an inhibition zone of 18.00 mm (MIC value of 86 μg/mL). The results of biofilm inhibition and hemolytic activity revealed that the SCFE method was superior to recover high quality EO in comparison to the HD method. The peppermint EO obtained by SCFE, owing to potent bioactive components, can be a potential candidate to develop nutra-pharmaceuticals.